Beyond social equity: Talking social justice in public administration. - Stivers, Camilla; Pandey, Sanjay K.; DeHart‐Davis, Leisha; Hall, Jeremy L.; Newcomer, Kathryn; Portillo, Shannon; Sabharwal, Meghna; Strader, Eiko; Wright, James (Public Administration Review, 2023)
SOCIAL JUSTICE IN PUBLIC ADMINISTRATION While public administration discourse has historically focused on social equity, social justice has been on the radar of social commentators for over 200 years. SOCIAL EQUITY IN PUBLIC ADMINISTRATION In public administration, the term social equity made its debut at the first Minnowbrook meeting in 1968, widely seen as the dawn of the "New Public Administration" movement. This editorial, featuring eminent public administration scholars in collaboration with PAR editors, builds on the PAR social equity legacy to argue for more intellectual discourse on social justice.[1] We collectively contend that social justice is an important focus for a scholarship as well as a guidepost of practical administrative ethics. A FRAMEWORK FOR SITUATING SOCIAL JUSTICE IN PUBLIC ADMINISTRATION Prominent literature streams in public administration often have implicit ideas about social justice, including assumptions about the status quo and limited conceptions of justice. Social equity scholarship has had a prominent place in public administration and in the pages of I Public Administration Review i (PAR) since 1974 when George Frederickson edited a PAR symposium on social equity.